A longitudinal study of three-dimensional pelvic behavior in maximal sprint running - Ota, K.; Maemura, H.; Tanigawa, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sprinting speed is determined by step frequency and step length, and there is an inverse relationship between step frequency and step length. It is important to increase step frequency while maintaining the large step length for achieving high sprinting speed. Improvement in the recovery of leg motion during sprinting results in an improvement in step frequency, and this motion is associated with the pelvis rotating to the free leg side (Sado et al., 2017). Sado et al. (2017) found that the pelvis rotates to the free leg side, which is associated with the greater free leg side lumbosacral joint torsional torque, assisting in the recovery of leg motion of the stance leg. Thus, it seems reasonable that the free leg side lumbosacral joint torsional torque during sprinting may have an important function in terms of achieving high sprinting speed. However, these findings were investigated cross-sectional in terms of the relationship between variables and differences in competition levels, and no longitudinal study has been reported to investigate changes in the factors influencing step frequency and step length with increasing sprinting speed. Therefore, the purpose of this study was conducted to investigate the longitudinal change in the kinematics and kinetics of the pelvis using data with the increasing sprinting speed.